Princípio da audição da criança - Gonçalves, Ricardo João Mota (2018)
This paper aims at exploring the importance of the child hearing as a paramount mechanism for the child to exert its opinion and to delimitate the content of its superior interest. The principle of the child hearing has a dual nature: the social hearing of the child and the judicial hearing of the child. Both sides in what regards this dual nature have great importance due to the fact that they contribute to shape the development of the child since its minority until becoming an adult. Therefore, we are prone to the implementation of the judicial child hearing in our judiciary system. The scope of this thesis also serves to highlight the necessity of a profound analysis in what concerns the legal dimension of the “superior child interest” problem. Hence the importance of approaching the Portuguese and international legal landscape in order to understand how the different legal mechanisms articulate themselves with the goal of protecting the superior interest of the child. For instance, in Portugal there’s a panoply of procedures, such as injunctions and interim orders, with the supreme goal of assuring the protection of the “superior child interest”. On that regard, the analysis of the Portuguese “Regime Geral do Processo Tutelar Cível”, enacted by the law No. 114/2015, September 8, is one of the main topics of this thesis. Its importance is justified by the fact that this legal regime not only regulates the subject of the judicial hearing of the child (direct regulation), but also regulates the procedures concerning the promotion and protection of endangered children and minors’ legal rights (regulated by remission). Finally, this thesis approaches the questions that somehow are still connected to the social hearing of the child, even the ones that don’t relate to the legality of the child’s right to be heard.